Application of CRISPR/Cas9 technology in sepsis research. (10th February 2020) - Wu, Miao; Hu, Niandan; Du, Xianjin; Wei, Jie
Abstract: CRISPR/Cas9, as a new genome-editing tool, offers new approaches to understand and treat diseases, which is being rapidly applied in various areas of biomedical research including sepsis field. The type II prokaryotic CRISPR/Cas system uses a single-guide RNA (sgRNA) to target the Cas9 nuclease to a specific genomic sequence, which is introduced into disease models for functional characterization and for testing of therapeutic strategies. This incredibly precise technology can be used for therapeutic research of gene-related diseases and to program any sequence in a target cell. Most importantly, the multifunctional capacity of this technology allows simultaneous editing of several genes. In this review, we focus on the basic principles, advantages and limitations of CRISPR/Cas9 and the use of the CRISPR/Cas9 system as a powerful tool in sepsis research and as a new strategy for the treatment of sepsis.